Lattice boltzmann method for crystallization processes - Aniruddha Majumder (2011)
Crystallization is a key unit operation used in several industries such as pharmaceutical, chemical and semiconductor industries. Like other particulate processes, the dynamics of crystallization processes can be described using population balance equations (PBEs). PBEs are integro-partial differential equations which take into account various ways (nucleation, growth, aggregation and breakage) in which particles of specific state can either form or deplete from a system. For most practical problems, PBEs do not have an analytical solution and thus need to be solved numerically.